Tata Kelola Pengadaan Barang Sahati Hotel - Sukma, Nilam; Nugraha, Rizki Nurul; Saraswati, Fannisa Rahayu; Putri, Naifa Ananda (Jurnal Ilmiah Wahana Pendidikan, 2023)
In Sahati Hotel operations, governance in the procurement of goods at the hotel is a process that involves various policies, procedures and practices to manage the procurement of goods needed by the hotel. The purchasing department has an important role in carrying out procedures for procuring goods for hotel needs. This aims to facilitate the operational process of the hotel. After the purchase of goods is made, the hotel provides a warehouse as a storage place for all goods managed by the storage department. Specifically, the receiver's job in the storage department is to receive ordered goods from the purchasing department. Purchasing goods is an important function in the operational success of the company. This function is responsible for obtaining materials of the right quantity and quality at the right time, and at the right price. Supervision also needs to be done to ensure the implementation of this function, because purchasing involves investing funds in inventory and the smooth flow of materials into the hotel. This study aims to evaluate the procedures for procuring goods at Sahati Hotel. How to identify the procurement system at the purchasing department of Sahati Hotel, how to manage the procurement of goods at the purchasing department of Sahati Hotel and why the governance of procurement of goods at the purchasing department of Sahati Hotel is very important. Data was collected through observation and interviews. The results of the research show that the procedures for procuring goods in the purchasing department have been carried out correctly, with the aim of improving service quality.